2021
DOI: 10.7759/cureus.16595
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressor-Induced Digital Ischemia

Abstract: In patients who are critically ill and in circulatory shock, substantial dosages of vasopressors including norepinephrine and Neosynephrine are often required to sustain blood pressure. While these medications are necessary and can be lifesaving, they are often associated with several complications related to severe vasoconstrictions. One of these known but underreported side effects is digital ischemia (DI). DI refers to a decrease in digital perfusion. It is a rare and uncommon phenomenon that can lead to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The first-line vasopressor NE indicated for the management of septic shock, with action on beta 1 adrenergic receptors and alpha-adrenergic receptors, stimulates the myocardium favoring cardiac output and increasing systemic blood pressure and coronary arterial flow. Peripheral digital ischemia occurs due to inadequate blood supply to digital tissue by sustained vasoconstriction, studies have shown that occlusion of small blood vessels is due to the drop in intraluminal pressure below 36 and 60 mmHg 5 decreasing blood flow to the extremities and causing such a complication, so it is important to publish this publication to guide health professionals on the subject and prevention of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…The first-line vasopressor NE indicated for the management of septic shock, with action on beta 1 adrenergic receptors and alpha-adrenergic receptors, stimulates the myocardium favoring cardiac output and increasing systemic blood pressure and coronary arterial flow. Peripheral digital ischemia occurs due to inadequate blood supply to digital tissue by sustained vasoconstriction, studies have shown that occlusion of small blood vessels is due to the drop in intraluminal pressure below 36 and 60 mmHg 5 decreasing blood flow to the extremities and causing such a complication, so it is important to publish this publication to guide health professionals on the subject and prevention of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…6 It also has beta-1 receptor agonist activity, which increases contractility of myocardial muscle fibers and heart rate, resulting in positive inotropic effects on the heart. 3,6 Phenylephrine is a non-catecholamine selective adrenergic agent with alpha-1 agonist activity that functions to increase vascular resistance. 7 Vasopressin is an antidiuretic hormone analog that promotes reabsorption of water in the kidney thus allowing the body to conserve water and raise blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…2 Vasopressor therapy is one of the important causes of digital ischemia, especially in the intensive care unit. 3 Herein, we report a young female with no past medical history who developed gangrene of bilateral feet secondary to vasopressor therapy initiated to sustain life following a serious motor vehicle crash, ultimately requiring transmetatarsal amputations. Interestingly, this patient did not have any pre-existing comorbidities, such as peripheral vascular disease or a history of smoking, which would increase her risk of vasopressor-induced ischemia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations